Cutaneous Metastasis in a Case of Adenocarcinoma of the Lung: A Cytological Diagnosis - Ashima Batra; Sant Prakash Kataria; Hemant Yadav; Rajeev Sen (Middle East Journal of Cancer, 2015)
Subcutaneous metastatic nodules are an uncommon first sign of underlying cancer. Cutaneous metastasis occurs in 0.8% to 4% of all cancer patients and less than 5% in those with lung cancer. These metastases are usually single or multiple painless nodules that may be mobile or fixed. Cutaneous metastases from the lung are not very common and indicate a worse prognosis. The limited literature on skin metastases from a primary lung suggests that if other extracutaneous metastases exist, median survival does not exceed three months; however, if the skin is the only site of metastatic disease, survival can reach ten months. Fine needle aspiration cytology is an excellent noninvasive method for early diagnosis of subcutaneous nodules, which in the presence of characteristic cytomorphology obviates the need for more invasive methods and surgery. Once diagnosed, the aim is to start treatment as soon as possible before widespread visceral metastases occur. Although the response to chemotherapy is poor, possibly due to poor blood supply to the skin, monitoring response to chemotherapy is easier when such lesions are present. We hereby describe the case of a 38-year-old male who presented with a mass in the right lung along with a nodule on his scalp. Fine needle aspiration cytology from both sites revealed cytological features of adenocarcinoma.